Electrical breakdown and chemical properties of polypropylene/calcium carbonate nanocomposites - A. Azmi; K. Y. Lau; N. A. Ahmad; Z. Abdul-Malek; C. W. Tan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Calcium carbonate (CaCO3) is an inorganic material which has been introduced in polymeric insulation to improve the thermal and electrical properties of insulation. In this research, a comparative study was performed between unfilled polypropylene (PP) and PP nanocomposites containing 5 wt% of CaCO3 nanofiller. The electrical breakdown performances of unfilled PP and nanocomposites were investigated. The chemical content of the material was carried out using fourier transform infrared (FTIR) spectroscopy. The findings showed that the introduction of CaCO3 to the PP altered the chemical bonding of the material, where two additional characteristic absorption bands appeared in the FTIR spectra of PP/CaCO3 nanocomposites. In addition, PP/CaCO3 nanocomposites had slight changes on the AC breakdown strength compared to unfilled PP. Meanwhile, the DC breakdown performance of the nanocomposites was apparently lower than that of unfilled PP. These were attributed to the agglomeration of CaCO3.